COVID-19 preventive social-behavioural practices and exposure to SARS-CoV-2 among residents in the city of Yaounde: Lessons from the early phase of the pandemic in Cameroon - Joseph Fokam; Alex Durand Nka; Jeremiah Efakika Gabisa; Kene Nwosu; Franck Wanda; Lucien Mama; Aude Christelle Ka'e; Yagai Bouba; Ezechiel Ngoufack Jagni Semengue; Michel Carlos Tommo Tchouaket; Désiré Takou; Aurelie minelle Kengni Ngueko; et al. (Public Library of Science (PLoS), 2023)
Non-pharmaceutical interventions remain key in mitigating the spread of SARS-CoV-2. We sought to assess COVID-19 preventive, social-behavioural practices, and SARS-CoV-2 exposure through IgG rapid tests. This was a cross-sectional survey among 971 respondents residing in 180 households within the "Cite Verte" health district of Yaounde-Cameroon, from October-November 2020. Using a structured questionnaire, data on SARS-CoV-2 preventive and social behavioural practices were collected, while exposure to SARS-CoV-2 was determined by IgG profiling. p<0.05 was considered statistically significant. Overall, 971 participants were enrolled, among whom 56.5% were females. The age group 15-29 (33.5%) and those with a secondary level of education (44.7%) were most represented. Regarding preventive/social behavioural practices, the least respected measure was "stopped work", 49.1%, while the most respected was "Respect of hygiene rules", 93.8%. Women obeyed preventive measures more than men, with 87.6% vs 81.0% adhering to the lockdown, (p = 0.005) and 95.5% vs 91.7% to hygiene rules (p = 0.017). The age range 45-64 years was the least adherent to the lockdown rule, with 75.2% (38/153), p<0.0001. Only 24.7% (73/295) and 6.1% (59/295) of the symptomatic individuals reported having sought medical consultation and Covid-19 testing respectively. In addition, up to 69.8% (555/795) felt healthcare facilities were high-risk sites for getting infected, p = 0.002. Exposure to SARS-CoV-2 by IgG positivity was 31.1% (302/971), with men recording a higher proportion of viral exposure, 51.0% (154/302), p = 0.021. After adjusting for gender, age, education, and occupation; salaried worker (p = 0.029; OR: 0.29), and trading (p = 0.001; OR: 0.23) least complied with lockdown rule. In this community of Cameroonian residents highly exposed to COVID-19, many perceived healthcare facilities as high-risk zones for SARS-CoV-2 infection and consequently did not seek medical interventions. Thus, in the context of such a pandemic, advocacy on risk communication and community engagement for health-seeking attitudes should preferentially target men and those afraid of pandemics.